Pengaruh Literasi Ekonomi dan Penyikapan Ulasan Pelanggan terhadap Perilaku Ekonomi Generasi Z dalam Pembelian Produk Fashion pada Aplikasi Shopee di DKI Jakarta - Firda Aulia Sani; Suparno Suparno; Fitra Dila Lestari (CV. Rumoh Aceh Publishing, 2026)
This study aims to describe the levels of economic literacy, customer review attitudes, and the economic behavior of Generation Z in purchasing fashion products through the Shopee application in DKI Jakarta, as well as to analyze the influence of economic literacy and customer review attitudes on the economic behavior of Generation Z. This study employed a quantitative approach with a causal associative research method. The population consisted of Generation Z individuals residing in DKI Jakarta who had purchased fashion products through the Shopee application within the last three months. A total of 225 respondents were selected using a purposive sampling technique. Data were collected through a questionnaire using a Likert scale and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with SmartPLS 4 software The results indicate that economic literacy, customer review attitudes, and the economic behavior of Generation Z are generally at a high level. The findings also reveal that economic literacy has a positive and significant influence on the economic behavior of Generation Z in purchasing fashion products through the Shopee application in DKI Jakarta. In addition, customer review attitudes have a positive and significant influence on economic behavior. The study further demonstrates that customer review attitudes exert a more dominant influence than economic literacy in shaping the economic behavior of Generation Z. Therefore, improving economic literacy and enhancing the ability to critically and rationally evaluate customer reviews are important factors in encouraging more prudent economic behavior when purchasing fashion products through the Shopee application.